Optimalisasi Restitusi dan Konstruksi Dakwaan bagi Anak Korban Prostitusi Online - Maharani, Putri; Rasdi Rasdi (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the implementation of legal protection for child victims of online prostitution, particularly in the fulfillment of restitution rights and the construction of indictments in criminal justice practice through the analysis of Decision Number 563/Pid.Sus/2023/PN Srg. This research employs a normative juridical method with statutory and case approaches. The findings reveal that the implementation of restitution as regulated under Government Regulation Number 43 of 2017 remains suboptimal, while the use of alternative indictments limits the scope of criminal liability and results in the failure to fulfill victims’ recovery rights. This condition reflects a gap between legal norms and judicial practice that has not fully adopted the principle of the best interests of the child. The study highlights that indictment construction plays a strategic role in shaping legal protection and the effectiveness of restitution fulfillment. The novelty of this research lies in examining the causal relationship between indictment construction and the fulfillment of restitution rights for child victims, as well as recommending cumulative or combined indictments to achieve victim-oriented substantive justice. Penelitian ini bertujuan untuk menganalisis implementasi perlindungan hukum terhadap anak korban prostitusi online, khususnya dalam pemenuhan hak restitusi dan konstruksi dakwaan dalam praktik peradilan pidana melalui studi Putusan Nomor 563/Pid.Sus/2023/PN Srg. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menunjukkan bahwa penerapan restitusi sebagaimana diatur dalam Peraturan Pemerintah Nomor 43 Tahun 2017 belum optimal, serta penggunaan dakwaan alternatif menyebabkan terbatasnya ruang pertanggungjawaban pelaku dan tidak terpenuhinya hak pemulihan korban. Kondisi ini menunjukkan adanya kesenjangan antara norma hukum dan praktik peradilan yang belum sepenuhnya berorientasi pada kepentingan terbaik bagi anak. Penelitian ini menegaskan bahwa konstruksi dakwaan memiliki peran strategis dalam menentukan arah perlindungan hukum dan efektivitas pemenuhan restitusi. Kebaruan penelitian ini terletak pada analisis relasi kausal antara konstruksi dakwaan dan pemenuhan hak restitusi anak korban dalam putusan pengadilan, serta rekomendasi penggunaan dakwaan kumulatif atau kombinasi sebagai upaya mewujudkan keadilan substantif yang berorientasi pada pemulihan korban.
Keywords: Perlindungan Anak; Prostitusi Online; Restitusi